Song of the tides : a novel - Joseph, Thomas A., 1950- (Fire ant books., 2008)
Beginning with their battle against the forces of Ponce de Leon, the Calusa Indians of southwest Florida entered a dark period of European invasion and native resistance, which changed the nature and course of life on the North American continent. This work is set during Spanish entrada into southwest Florida and their encounters with the Calusa.